On the Preschool Education of Children with Autism. The Current State of the Issue - Morozov, S.A. (Autizm i narušenie razvitiâ, 2023)
The main symptoms of autism takes long time to develop. Preschool education of children with autism spectrum disorders (ASD) is not only of psycho-educational and developmental importance, but also serves as the most important preventive factor. The proposed thematic issue «Preschool Education of Children with ASD: the Implementation of Adapted Educational Programs and the Application of Evidence-Based Practices» presents six articles on the actual issues of preschool education for children with autism spectrum disorders in Russia. Two articles deal with general issues (research and diagnosis of ASD), the authors of four other articles introduce the methods of teaching and support of preschool children. The possible prospects for further research and importance of the topics of publications are shown. Основные проявления аутизма формируются длительное время, и дошкольное образование детей с расстройствами аутистического спектра (РАС) имеет не только коррекционно-развивающее значение, но и служит важнейшим профилактическим фактором. Тематический выпуск журнала «Аутизм и нарушения развития» называется «Дошкольное образование детей с РАС: реализация адаптированных образовательных программ и применение доказательных практик». Журнал представляет шесть статей, посвященных актуальным вопросам дошкольного образования детей с расстройствами аутистического спектра в России. Две статьи посвящены общим вопросам (исследование и диагностика РАС), авторы четырех других статей знакомят читателей с методами обучения и сопровождения детей дошкольного возраста. Показана значимость тематики публикаций, возможные перспективы дальнейших исследований.